Le Discours historique de l’estat du royaume de Borno, genèse et construction d’une histoire du Borno par un captif de Tripoli au XVIIe siècle - Rémi Dewière (Afriques)
The Discours historique de l’estat du royaume de Borno, written by a former French slave in Tripoli in 1685, is one of the most important sources for the history of Borno sultanate. Unfortunately, its study has been neglected due to inconsistencies between the manuscript and other sources. The manuscript was then considered as a second hand source. However, a close study of the context where the manuscript was conceived and written shows that we can deeply learn from it. The work of whom we call the « French surgeon », comes within the scope of a context favorable for writing the experience of captivity. It is the consequence of the author’s intense works of research in Tripoli and in France. The « French surgeon » wrote this chapter in a voluminous manuscript on the history of Tripoli with the reviews of a second author. The most interesting part of his work remains the way how the « French surgeon » collected his sources : their census is the occasion to propose their first classification, and a first overview of the contribution of the Discours historique de l’estat du royaume de Borno for the modern history of Borno sultanate.